2014
DOI: 10.1371/journal.pone.0100893
|View full text |Cite|
|
Sign up to set email alerts
|

Long Non-Coding RNA BANCR Promotes Proliferation in Malignant Melanoma by Regulating MAPK Pathway Activation

Abstract: Long non-coding RNAs (lncRNAs) have been shown to be implicated in the complex network of cancer including malignant melanoma and play important roles in tumorigenesis and progression. However, their functions and downstream mechanisms are largely unknown. This study aimed to investigate whether BRAF-activated non-coding RNA (BANCR), a novel and potential regulator of melanoma cell, participates in the proliferation of malignant melanoma and elucidate the underlying mechanism in this process. We found that BAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 34 publications
1
139
1
2
Order By: Relevance
“…They found that BANCR knockdown reduced melanoma cell migration. Li et al (2014) further reported that BANCR was overexpressed in human malignant melanoma cell lines and tissues and increased expression with tumor stage (Li et al, 2014). Knockdown of BANCR suppressed melanoma cell proliferation via regulation of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 93%
“…They found that BANCR knockdown reduced melanoma cell migration. Li et al (2014) further reported that BANCR was overexpressed in human malignant melanoma cell lines and tissues and increased expression with tumor stage (Li et al, 2014). Knockdown of BANCR suppressed melanoma cell proliferation via regulation of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 93%
“…BANCR participates in the proliferation of malignant melanoma cells (7). BANCR regulates cellular proliferation and migration via p38 MAPK and c-Jun N-terminal kinase inactivation in lung carcinoma (LC) (8).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF-activated non-protein coding RNA (BANCR) is a 693-bp-long transcript on chromosome 9. It is frequently overexpressed and may be involved in the migration of melanoma cells (7). In non-small cell lung cancer, BANCR promotes the migration and invasion of cancer cells (8) through the mitogen-activated protein kinase (MAPK) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This link between BANCR and the MAPK pathways points to a novel mechanism in the regulation of melanoma proliferation. 75 In a previous section, it was mentioned that BRAF V600E was associated with increased EZH2 expression and H3K27 trimethylation of tumor suppressor genes. It will be interesting to see if there is any correlation between the expression of BANCR and EZH2 or poor prognosis.…”
Section: Braf-activated Non-coding Rna (Bancr)mentioning
confidence: 98%